The Simple Economics of Cybercrimes - Kshetri, Nir B. (IEEE security & privacy, 2006)
The characteristics of cybercriminals, cybercrime victims, and law enforcement agencies have a reinforcing effect on each other, leading to a vicious circle of cybercrime. The author builds on key elements of this circle to assess a hacker's cost-benefit calculus, and suggests possible mechanisms for combating cybercrim